Analisis Penyajian Laporan Keuangan, Aksesibilitas Informasi Keuangan dan Pengawasan Internal Terhadap Administrasi Keuangan Daerah di BPKPAD Kabupaten Sukoharjo - Andifa Nurul Hidayati (Jurnal Akuntansi dan Pajak, 2025)
This study aims to analyze the influence of financial statement presentation, information Financial accessibility, and internal control on the administration of regional financial management at the Regional Financial, Revenue, and Asset Management Agency (BPKPAD) of Sukoharjo Regency. The population in this study includes all employees of BPKPAD Sukoharjo, with a sample of 85 respondents determined using a saturated sampling technique. This research is a quantitative study. The analytical method used is based on primary data obtained through questionnaires, which were previously tested for validity and reliability. Hypothesis testing was conducted using multiple linear regression analysis, F-test, t-test, and the coefficient of determination test. The results of the study indicate that the presentation of financial statements has an effect on financial management administration, the accessibility of financial information has an effect on financial management administration, and internal control also affects financial management administration. These findings highlight the importance of the quality of financial statements, ease of access to financial information, and internal control systems in improving the accountability of regional financial management. Keywords : Accessibility Financial Information , Administration Regional Financial Management, Financial Statement Presentation, Internal Control.